THE CORRELATION BETWEEN VOCABULARY ABILITY OF THE FIRST YEAR STUDENTS OF ABDURRAB VOCATIONAL HIGH SCHOOL PEKANBARU AND THEIR READING COMPREHENSION IN NARRATIVE TEXT - Junita Sari; Indah Indah; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This research aimed to determine the correlation between the vocabulary ability of the first year students of Abdurrab Vocational High School Pekanbaru and their reading comprehension in narrative text. The sample of this research were 48 students. The sample was chosen by using Cluster Random Sampling Techniques. The data in this research were vocabulary and reading comprehension tests which were analyzed by Pearson Product Moment Formula in SPSS 23.0. The results of the study show that there was a correlation between vocabulary ability and reading comprehension in narrative text. The value of the correlation coefficient was 0.502. It was considered that the null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) was accepted. In scale correlation by Sugiyono (2010:231), 0.40 – 0.70 meant that the correlation between vocabulary ability of the first year students of Abdurrab Vocational High School Pekanbaru and their reading comprehension in narrative text categorized as intermediate correlation. In other words, the students’ vocabulary ability affects their reading comprehension.Key Words: Correlation, Vocabulary Ability, Reading Comprehension